Improved Torque Control Performance of Direct Torque Control for 5-Phase Induction Machine - Lourdes Victor Raj, Logan Raj; Jidin , Auzani; Abdul Karim, Kasrul; Sutikno, Tole; Sundram, Ramahlingam; JOPRI, MOHD HATTA (2013)
In this paper, the control of five-phase induction machine using Direct Torque Control (DTC) is presented. The general D-Q model of five-phase induction machine is discussed. The de-coupled control of stator flux and electromagnetic torque based on hysteresis controller similar to conventional DTC is applied to maintain the simplicity of the system. Three sets of lookup tables consist of voltage vectors with different amplitude that selects the most optimal voltage vectors according motor operation condition is proposed. This provides excellent torque dynamic control, reduces torque ripple, lower switching frequency (high efficiency) and extension of constant torque. Simulation results validate the improvement achieved.